Design and Evaluation of Floating Tablets of Glipizide Employing Olibanum Gum and Hydroxy Propyl Methyl Cellulose - Chowdary, K.P.R.; Swathi, G. (Asian Journal of Chemistry, 2010)
The objective of the study is to evaluate olibanum gum (a new natural gum resin) and hydroxy propyl methyl cellulose K15M as matrix formers for floating tablets on gas generating principle and to design floating tablets of glipizide. Floating tablets of glipizide were prepared employing olibanum gum and hydroxy propyl methyl cellulose as matrix formers and sodium bicarbonate as gas generating agent and the tablets were evaluated for in vitro buoyancy and drug release characteristics. Tablets formulated with hydroxy propyl methyl cellulose exhibited a floating time of more than 48 h with a floating lag time in the range of 18-54 s. Tablets formulated with olibanum gum also exhibited a floating time of more than 48 h but after a floating lag time of 1.0-1.5 h. Glipizide release from all the floating tablets formulated was slow, spread over more than 24 h and depended on the polymer used and its strength and concentration of the sodium bicarbonate in the tablet. Drug release was diffusion controlled and followed first order kinetics in the case of hydroxy propyl methyl cellulose tablets and zero order kinetics in the case of tablets prepared with olibanum gum. Fickain diffusion was the drug release mechanism from all the tablets formulated. Based on the in vitro buoyancy and drug release characteristics floating tablet formulation F6 (prepared using 50 % hydroxy propyl methyl cellulose and sodium bicarbonate 20 %) and F9 (prepared using 50 % olibanum gum and sodium bicarbonate 20 %) are considered as best floating tablets formulated and these formulations were found suitable for 24 h i.e., once-a-day administration.